Clinical aspects and therapeutic strategy in a case of urinary bladder endocervicosis - Diamantidis, Dimitrios; Tsakaldimis, Georgios; Georgellis, Chrysostomos; Lailisidis, Stavros; Panagiotopoulos, Nikolaos; Kafalis, Charalampos; Chousein, Chousein; Kouroupi, Maria; Deligeorgiou, Evangelia; Stamos, Charilaos; Giatromanolaki, Alexandra; Giannakopoulos, Stilianos; et al. (Menopause Review/Przegląd Menopauzalny, 2024)
The diagnostic complexities posed by lesions within the urinary bladder underscore the need for personalised management approaches. Endocervicosis, a rare condition stemming from Müllerian tissue, is characterised by the benign infiltration of endocervical glands, predominantly affecting the urinary bladder. Despite the absence of definitive symptoms, meticulous preoperative assessment is imperative to ensure precise diagnosis and optimal surgical intervention. While typically benign, recent cases have hinted at a potential association with adenocarcinoma, underscoring the necessity for meticulous management. The management of endocervicosis lacks consensus, with suggested surgical modalities including transurethral resection or partial cystectomy. In this case, a 47-year-old woman presented to our department with chronic pelvic pain following hysterectomy for adenomyosis. Imaging tests revealed a solid lesion situated at the dome of the urinary bladder. Consequently, a segmental cystectomy with circular tumour-only excision, with minimal free surgical margins, was undertaken to preserve bladder integrity. Histopathological analysis confirmed the diagnosis of endocervicosis. While the reported cases of urinary bladder endocervicosis remain limited, this instance contributes valuable insights into its understanding and management. It underscores the pivotal role of accurate diagnosis and tailored surgical intervention in optimising patient outcomes and mitigating postoperative complications, with tumour-only excision emerging as a promising and feasible approach.